Land Degradation Indicators: Spectral Indices - Chabrillat, Sabine (Annals of Arid Zone, 2016)
Desertification is a land ’degradation problem of major importance in the arid regions of the world. Deterioration in soil and plant cover has adversely affected nearly 70% of the drylands. Combating desertification involves having an accurate knowledge on current land degradation status and the magnitude of the potential hazard. The status of dryland systems is controlled to a large extent by a fragile equilibrium between soil, vegetation and water resources. Understanding of processes involves also the quantitative description of the interplay between soil and vegetation components. Dryland degradation may be triggered by (global) climatic change and/or human mismanagement. While the former may result in longer and more frequent drought events, the latter mainly consists of inappropriate land use practices. Both may induce changes in surface properties that can be detected remotely by measuring the spectral characteristics of the land surfaces from remote sensing data. Global soil and vegetation maps derived from satellite data are one of the primary sources of information for operational monitoring of the Earth. Advanced optical remote sensing techniques such as imaging spectrometry allows the determination of enhanced land degradation variables. It includes vegetation parameters and soil-related information such as green vegetation cover, senescent vegetation, leaf water content, photosynthetic pigments (chlorophyll, carotenoid, anthocyanins), foliage chemistry (nitrogen, cellulose), soil chemical properties (iron, organic matter, clay, carbonate content), soil moisture, salinity, detection of biological/structural crust, and runoff. These land sui-face variables can be directly linked to land degradation status. Spectral indices have been developed based on diagnostic features in the visible near-infrared (VNIR) and short wave infrared (SWIR) reflectance spectrum, allowing qualitative and quantitative description of the Earth’s surface changes in terms of bio- and geophysical/chemical properties, as a major step toward the quantitative monitoring of land degradation and desertification.